(untitled) (International Seven Journal of Health Research, 2023)
This article is about the Crisis Assistance Project implemented by a team from the professional groups of the Center of Formative Psychology® of Brazil during the COVID-19 pandemic in the year 2020. The services were done in the online mode, in the Formative Psychology® approach, founded by Stanley Keleman. The project aimed to offer people the means to regulate their emotional responses to the abrupt changes imposed by the pandemic, while learning to form adaptive solutions to the crisis.